Tourist Accommodation Facilities in the major Tourist Areas of Nepal - Sedai, Ram Chandra (Nepal Tourism and Development Review, 2013)
Accommodation sector constitutes one of the major components of tourism industry globally out of its popular 4 ‘A’ i.e. Attractions, Accessibility, Accommodation and Ancillary facilities. Accommodation sector, which is also considered as one of the major sub-sectors of tourism industry globally, has a huge potential to generate employment and income through the addition of values within its multiple layers of chains. Tourism accommodation is also one of the determinants of tourist choice for their destination. The overall objective of this article is to analyze and interpret the outcomes of the research study on tourist accommodation inventory carried out by NTB in June 2010, focusing on the capacity of tourism accommodation enterprises available in the major tourist areas of Nepal. More specifically, the article analyzes and interprets the findings of the research outcomes in the following aspects: Status of accommodation facilities by number of tourist enterprises, tourist rooms and tourist beds. Status of accommodation facilities by type and standard. Status of accommodation facilities by the status of registration. DOI: http://dx.doi.org/10.3126/ntdr.v1i1.7374 Nepal Tourism and Development Review Vol.1(1) 2011 102-123